2016
DOI: 10.1016/j.biopsycho.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Blunted neural response to errors as a trait marker of melancholic depression

Abstract: Identification of biomarkers of vulnerability for Major Depressive Disorder is a high priority, but heterogeneity of the diagnosis can hinder research. Biomarkers of vulnerability should also be present in the absence of the diagnosis. The present study examined the magnitude of the error-related negativity (ERN), an event-related potential component following errors in a sample with remitted melancholic depression (N=17), remitted non-melancholic depression (N=33), and healthy controls (N=55). Remitted melanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 115 publications
3
29
1
Order By: Relevance
“…In particular, future studies using a neutral stress condition are needed to rule out the possibility that our effects are not simply due to practice or fatigue. Additionally, although we observed no group differences in ERN amplitude, recent research using the Flanker task found that only rMDD individuals with prior melancholic depression, showed blunted ERN amplitudes (Weinberg et al, 2016). Unfortunately the SCID-IV assessment only captures MDE specifiers for current depressive episodes, so we were unable to classify our rMDD sample into melancholic versus non-melancholic subtypes to address this question.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In particular, future studies using a neutral stress condition are needed to rule out the possibility that our effects are not simply due to practice or fatigue. Additionally, although we observed no group differences in ERN amplitude, recent research using the Flanker task found that only rMDD individuals with prior melancholic depression, showed blunted ERN amplitudes (Weinberg et al, 2016). Unfortunately the SCID-IV assessment only captures MDE specifiers for current depressive episodes, so we were unable to classify our rMDD sample into melancholic versus non-melancholic subtypes to address this question.…”
Section: Discussioncontrasting
confidence: 90%
“…Specifically, whereas some studies have demonstrated an increased ERN amplitude in MDD (Chiu and Deldin, 2007; Holmes and Pizzagalli, 2008), others have found ERN reduction in severely depressed samples (Schrijvers et al, 2008; Olvet et al, 2010), suggesting that the relationship between ERN amplitude and depression severity may be non-linear (Olvet et al, 2010). An alternative explanation is that differences arise due to diagnostic heterogeneity, as blunted ERN amplitudes have been linked with psychomotor retardation (Schrijvers et al, 2008), and the melancholic depression subtype (Weinberg et al, 2016). The lack of group differences in scalp-level ERN and Pe amplitudes must be interpreted with caution however, as our sample of subjects with sufficient artifact-free ERP data at both pre- and post-stress, was smaller than prior studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bracht et al (2014) recently found that relative to controls and those with nonmelancholic MDD, melancholic MDD was associated with reduced white matter integrity in the medial forebrain bundle, a key white matter track for reward processing and dopamine transmission. Relatedly, dopamine plays an important role in the pursuit of rewards (Treadway & Zald, 2011) and dopaminergic abnormalities appear to be particularly prevalent in those with melancholic depression (Parker, 2007; Parker et al, 1995; Weinberg, Liu, & Shankman, 2016). Interestingly, asymmetry of D2 receptor availability within the striatum was found to be associated with motivation and distinction between reward and punishment such that greater motivation was associated with higher dopamine receptor availability in the left relative to right striatum (Tomer et al, 2008; 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Results from other tasks will be reported elsewhere (e.g., Gorka et al, 2015; Weinberg, Liu, & Shankman, 2015). The present task was administered on a Pentium class computer, using the stimulus presentation software Presentation (Neurobehavioral Systems, Inc.).…”
Section: Methodsmentioning
confidence: 99%